Quantitative carcass traits from buffaloes of three genetic groups finished in feedlot and slaughtered at different stages of maturity - Jorge, Andre Mendes [UNESP] (2004)
UNESP, FMVZ DPEA Botucatu, Botucatu, SP, Brazil